Ways of examining speech acts in young african american children: considering inside-out and outside-in approaches. - Dejarnette, Glenda; Rivers, Kenyatta O; Hyter, Yvette D (Topics in Language Disorders, 2015)
To develop a framework for further study of pragmatic behavior in young children from African American English (AAE) speaking backgrounds, one aspect of pragmatic behavior is explored in this article, specifically, speech acts. The aims of this article are to (1) examine examples of how external taxonomies (i.e., an “etic” or “outside-in” approach) have been applied to the speech act behavior of AAE child speakers and to note that etic approaches alone do not identify cultural characteristics that influence the presentation of speech acts in this population; (2) conceptualize a culture-sensitive framework where components of AAE speech act behaviors can be identified as gleaned from existing linguistic research; and (3) explain the utility of analyses of speech act behavior using taxonomies that have emerged from the cultural language style of AAE speakers, that is, an “emic” or “inside-out” approach.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-681-907-287-000 tex.type: [object Object]
Keywords: English speakers; communicative functions; dept.cmd; language behavior; pragmatic behavior; speech acts; young African American